A three-day anatomy revision course taught by senior peers effectively prepares junior students for their national anatomy exam - Rengier, Fabian; Rauch, Philipp; Partovi, Sasan; Kirsch, Joachim; Nawrotzki, Ralph (Annals of anatomy, 2010)
Objectives - This study examines whether peer-teaching, in the setting of a three-day revision course in anatomy, is effective in preparing medical students for their national anatomy exam. - Methods - The anatomy course was designed for candidates taking the first part of the German national medical exam. Increase of knowledge during the course was assessed by tests before and after the course (group A). To test equivalence, two control groups participated in the pre-test (group B) or in the course and in the post-test (group C). Participants anonymously rated 14 feedback items on a five-point Likert scale ranging from 1 (full agreement) to 5 (full disagreement). - Results - Group A students’ performance improved significantly during the course with a mean increase of 7.15 points (11.9% improvement; p<0.001). Equivalence testing showed that performance of group A students in the pre-/post-tests was equal to those of group B pre-tests and group C post-tests, respectively. Agreement on the 14 feedback items was highly significant (p<0.001 for all items), with a global median of 1. - Conclusions - This study shows that a three-day anatomy revision course is effective and highly appreciated by medical students in their preparation for the national exam. Moreover, peer-teaching is reliable at this stage of the medical curriculum.